Can anti-Müllerian hormone predict success outcomes in donor sperm inseminations?. (2nd January 2019) - González-Foruria, Iñaki; Martínez, Francisca; Rodríguez-Purata, Jorge; Ballester, Marta; Alonso-Mosquera, Verónica; Buxaderas, Rosario; Rodríguez, Ignacio; Coroleu, Buenaventura
Abstract: Anti-Müllerian hormone (AMH) is a useful biomarker to predict the ovarian response to controlled ovarian stimulation (COS) for IVF. However, currently there is a lack of evidence for the role of ovarian reserve markers when there is no need of COS. The aim of this study was to evaluate the usefulness of AMH to predict the outcomes of donor sperm insemination cycles in non-infertile women. A retrospective study including 139 healthy women, who underwent 348 intrauterine insemination (IUI) cycles with donor sperms under the stimulated or natural cycles, was conducted. All patients had an AMH evaluation performed before starting the first IUI attempt. AMH levels were similar in both, women who conceived and those who did not (2.00 ± 1.52 vs. 1.88 ± 1.64 ng/ml; p  = .45). The area under the ROC curve in predicting pregnancy for AMH was 0.53. After adjusting for other confounding variables, the multivariate analysis revealed that AMH was not associated with pregnancy (aOR 0.89; 95% CI 0.57–1.37). We conclude that AMH is not predictive of pregnancy in healthy non-infertile women who perform IUI with donor sperm. These findings suggest the low capability of AMH to predict fertility when no COS is needed.